PENGARUH PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN SHOPEE PAYLATER DENGAN VARIABEL MODERATING BEHAVIOURAL INTENTION - Octoviani, Aniza (Jurnal Ekonomi Bisnis Manajemen Prima, 2024)
Technological developments and the pandemic that has occurred encourage e-commerce to increase creativity by providing convenience, one of which is convenience in the payment system, which is using the paylatter payment system. This research tries to see whether paylatter can increase consumer decisions in making purchases in e-commerce. The data was taken using a survey method and processed using the SEM method. From the results of data processing, we find that consumer purchasing decisions are not influenced by the perceived ease of use of paylatter, while perceived benefits have an influence on the decision to use paylatter.